Digital Literacy in Arabic Language Learning in Madrassas Aliyah 2 Tanah Datar : Literasi Digital dalam Pembelajaran Bahasa Arab di Madrasah Aliyah 2 Tanah Datar - Eri Ramadona; Aida Fitria; Irwandi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2023)
The research is to find out how digital literacy is applied to Arabic language learning in madrasas. The qualitative research method was used where the data was taken from interviews and observation. The informants of the research involved three Arabic language teachers and 30  grade 11 students selected randomly. The research showed that the use of digital literacy in Arabic language learning at State Madrasah Aliyah 2 had been used well and had a positive impact on students' interest in understanding Arabic language material provided by the teachers. Students are generally more enthusiastic, more creative, and more challenged to learn Arabic using digital learning media.  The digital media used in the madrasah are InFocus projectors, laptops, and Android cellphones using the applications available on the media platform. For example, WhatsApp, YouTube, TikTok, Kahoot, and Quiziz applications. The research recommended, Increasing the procurement of projectors in each classroom and increasing the internet connection in schools to make it more stable so that it can be easily accessed by teachers and students in the learning process. Keywords: Arabic, Digital Literacy, Literacy   Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana literasi digital diterapkan dalam pembelajaran bahasa Arab di madrasah. Metode penelitian yang digunakan adalah kualitatif dimana data diambil dari wawancara dan observasi. Informan penelitian ini melibatkan tiga orang guru bahasa Arab dan 30 orang siswa kelas 11 yang dipilih secara acak. Hasil penelitian menunjukkan bahwa pemanfaatan literasi digital dalam pembelajaran bahasa Arab di Madrasah Aliyah Negeri 2 telah dimanfaatkan dengan baik dan memberikan dampak positif terhadap minat siswa dalam memahami materi bahasa Arab yang diberikan oleh guru. Siswa umumnya lebih antusias, kreatif dan tertantang untuk belajar bahasa Arab dengan menggunakan media pembelajaran digital. Media digital yang digunakan di madrasah adalah proyektor infocus, laptop, handphone android dengan menggunakan aplikasi yang tersedia pada platform media. Misalnya saja aplikasi WhatsApp, YouTube, Tiktok, Kahoot dan Quiziz. Penelitian ini merekomendasikan, menambah pengadaan alat proyektor di setiap kelas dan menambah koneksi internet disekolah agar lebih stabil, sehingga dapat dengan mudah di akses oleh guru dan siswa dalam proses pembelajaran. Kata Kunci: Bahasa Arab, Literasi, Literasi Digital